1982
DOI: 10.1177/106002808201601102
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Drug Withdrawal Syndrome

Abstract: After discontinuation of antihypertensive medications, patients may experience symptoms associated with catecholamine excess, with or without a rapid rise in blood pressure; this is referred to as antihypertensive drug withdrawal syndrome. Though most often associated with the discontinuation of clonidine, this syndrome has been reported to follow the withdrawal of many other antihypertensives. Proposed mechanisms for the syndrome, depending on the drug involved, include enhanced activity of (1) the sympathoad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…(OVERSTREET and YAMAMURA 1979;PARKER and ATKINSON 1982;CUMMINGS and VLASSES 1982 ). It has been suggested that these processes may be involved in the development of, on the one hand, tolerance -after exposure to agonists-and on the other hand rebound or withdrawal phenomena after receptor blockade.…”
Section: Iatrogenic Receptor Imbalancementioning
confidence: 99%
“…(OVERSTREET and YAMAMURA 1979;PARKER and ATKINSON 1982;CUMMINGS and VLASSES 1982 ). It has been suggested that these processes may be involved in the development of, on the one hand, tolerance -after exposure to agonists-and on the other hand rebound or withdrawal phenomena after receptor blockade.…”
Section: Iatrogenic Receptor Imbalancementioning
confidence: 99%
“…In patients concomitantly receiving β-adrenergic blockers and clonidine, the β-adrenergic blocker should be withdrawn at least five half-lifes prior to introduction of clonidine, otherwise the initial unopposed α-adrenergic stimulation may result in hypertensive crisis [109,110].…”
Section: Clonidinementioning
confidence: 99%
“…Clonidine [109,110] Unopposed α-adrenergic stimulation upon β-adrenergic blocker withdrawal Hypertensive crisis…”
Section: Renal Eliminationmentioning
confidence: 99%
“…15 Withdrawal from clonidine is associated with rebound hypertension. 16 This has not yet been studied with dexmedetomidine. We now know a lot about the safety of individual sedative agents and a little about their safe use in the critically ill. We need to know a lot more about dexmedetomidine before we can use it with con®dence.…”
mentioning
confidence: 99%